Towards coupling full-disk and active region-based flare prediction for operational space weather forecasting - Pandey, Chetraj; Ji, Anli; Angryk, Rafal A.; Georgoulis, Manolis K.; Aydin, Berkay (Frontiers in Astronomy and Space Sciences, 2022)
Solar flare prediction is a central problem in space weather forecasting and has captivated the attention of a wide spectrum of researchers due to recent advances in both remote sensing as well as machine learning and deep learning approaches. The experimental findings based on both machine and deep learning models reveal significant performance improvements for task specific datasets. Along with building models, the practice of deploying such models to production environments under operational settings is a complex and often time-consuming process which is often not addressed directly in research settings. We present a set of new heuristic approaches to train and deploy an operational solar flare prediction system for ≥M1.0-class flares with two prediction modes: full-disk and active region-based . In full-disk mode, predictions are performed on full-disk line-of-sight magnetograms using deep learning models whereas in active region-based models, predictions are issued for each active region individually using multivariate time series data instances. The outputs from individual active region forecasts and full-disk predictors are combined to a final full-disk prediction result with a meta-model. We utilized an equal weighted average ensemble of two base learners’ flare probabilities as our baseline meta learner and improved the capabilities of our two base learners by training a logistic regression model . The major findings of this study are: (i) We successfully coupled two heterogeneous flare prediction models trained with different dataset and model architecture to predict a full-disk flare probability for next 24 hours, (ii) Our proposed ensembling model, i.e., logistic regression, improves on the predictive performance of two base learners and the baseline meta learner measured in terms of two widely used metrics: True Skill Statistic (TSS) and Heidke Skill Score (HSS), and (iii) Our result analysis suggests that the logistic regression-based ensemble (Meta-FP) improves on the full-disk model (base learner) by ~9% in terms of both the TSS and HSS. Similarly, it improves on the AR-based model (base learner) by ~17% and ~18% in terms of TSS and HSS respectively. Finally, when compared to the baseline meta model, it improves on TSS by ~10% and HSS by ~13%.